Dominance of filariasis vector spread in endemic regions of Indonesia - Ghani, Zhakia Rahma; Lukiyono, Yauwan Tobing (Universitas Nahdlatul Ulama Surabaya, 2025)
The number of filariasis cases in Indonesia is increasing every year. This is especially true for people living in mosquito breeding areas, both artificial and natural, coupled with low knowledge and awareness of personal and environmental hygiene. The results of this review of various sources are expected to provide input for policy makers in mapping and determining filariasis vectors, so that vector control efforts can be carried out in an appropriate manner to break the chain of transmission and achieve the elimination target of this disease. This study used a systematic review method. The data used were secondary data in the form of research results published in electronic journals. Culex sp. has a wide distribution area and was found in every study, even dominating 8 out of 13 studies conducted. In general, the spread of filariasis disease in the tropics and subtropics, especially in countries with a middle to lower income index. Given this, it is important to map the distribution of filariasis vectors by geographical region, as it can help identify areas that require special treatment.